Analysis in Choroidal Thickness in Patients with Graves’ Ophthalmopathy Using Spectral-Domain Optical Coherence Tomography - Nan Yu; Yadi Zhang; Lei Kang; Ying Gao; Junqing Zhang; Yuan Wu (Journal of Ophthalmology)
Objectives. The objective of the study is to observe changes in choroidal thickness (CT) in patients with Graves’ ophthalmopathy using spectral-domain optical coherence tomography (SD-OCT). Methods. The right eyes of 36 patients (27 females and 9 males) with Graves’ ophthalmopathy (GO) and those of 36 age-, gender-, and diopter-level-matched healthy participants were evaluated. The patients’ data were obtained within 3 months after the onset of Graves’ disease (GD). Thyroid hormone levels and thyroid-stimulating hormone receptor antibody (TRAb) levels were measured, and the degree of exophthalmos was measured in all patients. Activity is measured by the clinical activity score (CAS). A horizontal scan centered on the fovea was performed in all participants. Five points of choroidal thickness were measured at the fovea (SFCT) and at 1500 μm nasal (N1500), 3000 μm nasal (N3000), 1500 μm temporal (T1500), and 3000 μm temporal (T3000) to the fovea. Results. The CT measurements obtained were (mean ± SD) 313.47 ± 100.32 μm, 279.22 ± 85.80 μm, 214.64 ± 75.52 μm, 313.19 ± 80.36 μm, and 298.14 ± 82.75 μm in patients with GO and were 256.33 ± 50.18 μm, 223.14 ± 59.61 μm, 176.69 ± 60.66 μm, 250.92 ± 52.184 μm, and 239.47 ± 60.35 μm in the control group at the foveal, N1500, N3000, T1500, and T3000 measurement points, respectively. The CT in GO patients was significantly increased at all the points compared with the control group (P<0.05). There was no relationship between the CT and CAS, the degree of exophthalmos, triiodothyronine (T3), tetraiodothyronine (T4), thyroid-stimulating hormone (TSH), or TRAb levels in GO. Conclusions. CT was found to be increased in GO patients and had poor relationship with CAS, exophthalmos, and thyroid function tests.